Moringa oleifera leaf extract restored the diameter and epithelium thickness of the seminiferous tubules of rat (Rattus norvegicus) injected with gentamicin - Mardatillah, Meidy; Wurlina, Wurlina; Yudaniayanti, Ira Sari; Primarizky, Hardany; Plumeriastuti, Hani; Hamid, Iwan Sahrial (Universitas Airlangga, 2022)
This research aims to determine the effect of Moringa oleifera leaf extract (MLE) on the diameter and epithelium thickness of the seminiferous tubules of rats induced with gentamicin. This study used 25 male rats (Rattus norvegicus) aged 8-12 weeks with 150-200 grams body weight. Negative control group (C-) was injected with aquadest and given 0.5% Na-CMC orally, positive control group (C+) was induced with gentamicin injection of 5 mg/kg BW/day and given 0.5% Na-CMC orally, while groups T1, T2, and T3 were induced with gentamicin at the same dose and treated orally with MLE of 200, 316, 500 mg/kg BW/day. Analysis of variance showed significant differences and further analysis using Duncan Multiple Range Test showed difference in each group. The results showed that treatment with MLE of 500 mg/kg BW/day improved the diameter and epithelium thickness of the seminiferous tubules of rats injected with gentamicin. It could be concluded that MLE restored the diameter and epithelium thickness of the seminiferous tubules of rats induced with gentamicin.